Pendampingan Diversifikasi Dan Diversitas Dan Diversitas Produk Pandan Pada UMKM Di Desa Wisata Cupak Kabupaten Jombang - Irda Agustin Kustiwi; Cholis Hidayati (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
In today's increasingly sophisticated era, MSMEs must be able to compete with entrepreneurs who are increasingly creative and trained to use modern technologies. One of the things that can help these MSMEs is by assisting in product diversification and diversity. This article aims to determine the impact obtained by MSMEs in Cupak Village, Jombang after training and mentoring. The research was conducted in 3 ways, namely observation, interviews, and surveys on MSMEs in Cupak village, Jombang. This research will result in increasing the expertise of MSMEs and enabling MSMEs to reach a wider market.